Agency, autonomy and consent: cues from the neuroscience of self-control - Sirgiovanni, Elisabetta (Studia Bioethica, 2019)
In this paper I intend to focus on common alterations and distortions to an informed, voluntary, and decisionally-capacitated consent in the medical setting, especially those that impact the patient’s decision-making process. In doing so, I will focus on two specific issues. On the one hand, I will examine cognitive biases and self-deceptive processes that may affect the patient’s choice and autonomy. On the other hand, I will discuss the capacity of self-government as what usually referred to as the neurocognitive capacity of self-control. My view thus consists of two main claims: that even in capacitated individuals, consent to treatment/research is not necessarily identifiable as fully rational and deliberative choice; however, that empirical literature about self-control may shed some light on how to improve informed consent procedures as such.